Profile of women submitted to tubal laqueuration in public maternity in the municipality of Palmas, Tocantins (Research, Society and Development, 2022)
Introduction: Tubal sterilization emerged as a method of fertility control and is a surgery for definitive sterilization. Female sterilization is one of the most effective methods, with a low risk of failure, with less than one pregnancy per 100 women occurring in the first year after the sterilization procedure (5 per 1,000). Objective: To analyze the profile of women undergoing tubal ligation at Hospital Maternidade Dona Regina Siqueira Campos (HMDR) in 2021 in Palmas, Tocantins, Brazil. Methods: Descriptive and documentary study, with a cross-sectional quantitative and qualitative approach, and the study was based on data from the statistical analysis sector of the Hospital e Maternidade Dona Regina (HMDR) of women who underwent tubal ligation in the year 2021 Results: Of the 409 In the analyzed sterilization patients, more than half were in a union – married or in a stable union, and the rest were single or divorced women. The average age of women who underwent the tubal ligation procedure in the city of Palmas-TO was 32.3 years. The highest incidence occurred between the ages of 31 to 35 years and the lowest between 19 to 21 years. In all age groups, the average number of pregnancies of the 409 women analyzed in the study was greater than 3. Conclusion: The women's lack of knowledge about the family planning law nº 9.263/96 may explain the high rate of choice of performing the tubal ligation procedure as a contraceptive method.